Utilizing Instagram for Digital Government Public Relations by Diskominfo Jatim - Teguh, Monika; Qotrunnada, Namira Al; Calysta, Keisya; Bungin, Burhan; Ahmad, Mohd Khairie (Komunikator, 2024)
In addressing the challenges of the PR 4.0 era, the East Java Communication and Information Office (Diskominfo) utilizes the Instagram account @jatimpemprov to carry out Digital PR activities. The account serves as a communication platform to present essential information and is expected to be a solution, particularly for the people of East Java. These activities have proven successful in conveying information, aspirations, and programs that reach the public. Therefore, this research aims to understand how Digital PR activities are carried out by Diskominfo Jatim through the Instagram account @jatimpemprov. The theoretical framework used to examine the phenomena in this study is the principles of the 7-Cs PR communication model, which includes credibility, context, content, clarity, continuity & consistency, channel, and the capability of the audience. This research employs a descriptive qualitative method. Data collection was carried out through structured interviews and document studies. The results show that the digital PR activities of @jatimpemprov apply the principles of the 7-Cs PR Communications model by utilizing Instagram features. These activities provide informative, educational, and entertaining content to the public. The main functions of disseminating information and fostering cooperation between other organizations within the East Java Provincial Government are carried out effectively.